Penerapan Project-Based Learning dalam Kurikulum Merdeka dengan Pendekatan Pembelajaran Mendalam dalam Upaya Meningkatkan Keterampilan Speaking Siswa SMK - Septian Aep Nugraha (Jurnal Riset dan Transformasi Pendidikan, 2026)
This study aims to examine the effect of implementing Project-Based Learning (PjBL) within the Merdeka Curriculum using a deep learning approach on improving students’ speaking skills at a Vocational High School (SMK). The research employed a quasi-experimental design with a non-equivalent control group. The participants consisted of two classes: an experimental class taught using PjBL with a deep learning approach and a control class taught using conventional instruction. Data were collected through speaking tests (pre-test and post-test), classroom observations, and documentation. The data were analysed using descriptive statistics and inferential analysis to determine differences in speaking skill improvement between the two groups. The findings indicate that the experimental class showed a significantly greater improvement in speaking skills compared to the control class. The implementation of PjBL enhanced students’ active engagement, confidence, fluency, pronunciation accuracy, and grammatical use through contextual project activities relevant to workplace needs. Therefore, it can be concluded that Project-Based Learning within the Merdeka Curriculum using a deep learning approach has a positive and significant effect on improving vocational students’ speaking skills.